Relative Hypoglycemia in Diabetic Patients With Critical Illness. Issue 3 (March 2020) - Kwan, Timothy N.; Zwakman-Hessels, Lara; Marhoon, Nada; Robbins, Ray; Mårtensson, Johan; Ekinci, Elif; Bellomo, Rinaldo
Abstract : Objectives: Relative hypoglycemia is a decrease in glucose greater than or equal to 30% below prehospital admission levels (estimated by hemoglobin A1C) but not to absolute hypoglycemia levels. It is a recognized pathophysiologic phenomenon in ambulant poorly controlled diabetic patients but remains unexamined during critical illness. We examined the frequency, characteristics, and outcome associations of relative hypoglycemia in diabetic patients with critical illness. Design: Retrospective cohort study. Setting: ICU of a tertiary hospital. Patients: One-thousand five-hundred ninety-two critically ill diabetic patients between January 2013 and December 2017. Interventions: None. Measurements and Main Results: The median age of patients was 67 years (interquartile range, 60–75 yr). The median Acute Physiology and Chronic Health Evaluation III score was 53 (interquartile range, 40–68). Thirty-four percent of patients with diabetes experienced relative hypoglycemia (exposure) during their ICU admission. Such patients had higher glycemic lability, hemoglobin A1C levels, and Acute Physiology and Chronic Health Evaluation III scores. The hazard ratio for 28-day mortality of diabetic patients, censored at hospital discharge, for patients with relative hypoglycemia was 1.9 (95% CI, 1.3–2.8) and was essentially unchanged after adjustment for episodes of absolute hypoglycemia. After an episode of relative hypoglycemia, the hazard ratio for subsequent absolute hypoglycemia in the ICU was 3.5 (95% CI, 2.3–5.3). Conclusions: In ICU patients with diabetes, relative hypoglycemia is common, increases with higher hemoglobin A1C levels, and is a modifiable risk factor for both mortality and subsequent absolute hypoglycemia. These findings provide the rationale for future interventional studies to explore new blood glucose management strategies and to substantiate the clinical relevance of relative hypoglycemia. Abstract : Supplemental Digital Content is available in the text.